In the context of mixture models in Bayesian inference, one can assume that the general form of the joint posterior for a mixture model of $k$ components is

$$ \begin{equation} p( \boldsymbol{\lambda} , \boldsymbol{\theta} \mid \boldsymbol{y}) \propto \bigg[ \prod_{i=1}^{n} \sum_{j=1}^{k} \lambda_{j} f(y_{i} \mid \boldsymbol{\theta}_{j} ) \bigg] \ p(\boldsymbol{\lambda} ,\boldsymbol{\theta} ) \ . \end{equation} $$

Incorporating information about the missing variable $Z$ and thus using the augmented likelihood, the posterior accounting for the complete data structure reads (this formula is given in the excellent book "Bayesian Core" by Marin and Robert (2007))

$$ \begin{equation} p(\boldsymbol{\theta}, \boldsymbol{\lambda} \mid \boldsymbol{y}, \boldsymbol{z}) \propto \bigg[ \prod_{i=1}^{n} \prod_{j=1}^{k} \lambda_{ j}^{z_{ij}} f (y_{i} \mid \boldsymbol{\theta}_{j})^{z_{ij}} \bigg] \ \ p(\boldsymbol{\lambda} ,\boldsymbol{\theta} ) \ . \end{equation} $$

However, one can assume the following model decomposition for the joint posterior of all variables if we use independent prior for $\boldsymbol{\theta} = (\boldsymbol{\mu}, \boldsymbol{\sigma}^{2})$. $$ p(\boldsymbol{y}, \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2}) = p(\boldsymbol{y} \mid \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma^{2}}) \ p(\boldsymbol{z} \mid \boldsymbol{\lambda}) \ p(\boldsymbol{\lambda}) \ p(\boldsymbol{\mu}) \ p(\boldsymbol{\sigma^{2}}) \\ = p(\boldsymbol{y} \mid \boldsymbol{\Psi}) \ p(\boldsymbol{\Psi}) \ .\\ $$

where $\boldsymbol{\Psi} = (\boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma^{2}})$

I find it hard to see how the expression $p(\boldsymbol{\theta}, \boldsymbol{\lambda} \mid \boldsymbol{y}, \boldsymbol{z}) $ relates to $p(\boldsymbol{y}, \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2})$. Any hints ?

  • $\begingroup$ can you point us to the section & page? I'm having hard time to understand variable $z$, exponentiation, and conversion of inner summation to inner multiplication. $\endgroup$
    – gunes
    Commented Jan 17, 2019 at 15:00
  • $\begingroup$ Its on chapter 6, p. 151, but the author writes the likelihood with subscripts, that is $ \prod_{i=1}^{n} p_{z_{i}} f(y_{i} \mid \theta_{z_{i}})$. The $z_{i}$ comes from a multinomial distribution of parameter $\lambda_{j}$, for $j=1,...,k$ and it is inspired from the way we write a likelihood for a bernoulli distribution. This formula for the likelihood comes from the book "Modèles à variables latentes et modèles de mélange" from Droesbeke, Saporta and Thomas-Agnan. $\endgroup$
    – julian
    Commented Jan 17, 2019 at 15:18

1 Answer 1


Thank you for the appreciation of our book! By Bayes' formula, the posterior density $$p(\boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2}|\boldsymbol{y}, \boldsymbol{z})$$ is proportional to the joint density $$p(\boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2}|\boldsymbol{y}, \boldsymbol{z})\propto p(\boldsymbol{y}, \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2})$$ which itself decomposes into $$p(\boldsymbol{y}, \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2}) = \overbrace{p(\boldsymbol{y} \mid \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma^{2}})}^\text{completed model} \ \overbrace{p(\boldsymbol{z} \mid \boldsymbol{\lambda})}^\text{latent model} \ \overbrace{p(\boldsymbol{\lambda}) \ p(\boldsymbol{\mu}) \ p(\boldsymbol{\sigma^{2}})}^\text{prior} $$ and also $$p(\boldsymbol{y}, \boldsymbol{z}, \boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2})= p(\boldsymbol{y}, \boldsymbol{z} \mid \boldsymbol{\Psi}) \ p(\boldsymbol{\Psi}) \ .\\$$ where $$\boldsymbol{\Psi}=(\boldsymbol{\lambda}, \boldsymbol{\mu}, \boldsymbol{\sigma}^{2})=(\boldsymbol{\lambda}, \boldsymbol{\theta})$$ (The $\boldsymbol{z}$ is missing in the second row of your equation.)

Note: The representation of the likelihood is much older than the book "Modèles à variables latentes et modèles de mélange" from Droesbeke, Saporta and Thomas-Agnan. See for instance Dempster, Laird and Rubin (1979).

  • 1
    $\begingroup$ Thank you for this answer @Xi'an. Your explanation is very clear and useful. $\endgroup$
    – julian
    Commented Jan 23, 2019 at 8:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.